Case report: Success of allogeneic hematopoietic stem cell transplantation for refractory systemic-onset juvenile idiopathic arthritis - Beaufils, Camille; Proulx, Catherine; Blincoe, Annaliesse; Teira, Pierre; Bittencourt, Henrique; Cellot, Sonia; Duval, Michel; Morin, Marie-Paule; De Bruycker, Jean Jacques; Couture, Julie; Samaan, Kathryn; Decaluwe, Hélène; et al. (Frontiers in Medicine, 2023)
Objectives: This study reports cases of systemic-onset juvenile idiopathic arthritis (sJIA) who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) at our center and reviews published outcomes of allo-HSCT in sJIA. Methods: Case report of two sJIA who underwent allo-HSCT at a tertiary pediatric hospital. Patients' disease course, allo-HSCT protocol/outcome are described. Outcomes of published cases of allo-HSCT in sJIA were compared to our experience. Results: Two patients with sJIA had allo-HSCT. Both failed multiple lines of disease modifying anti-rheumatic drugs and experienced severe disease/treatment-related complications. Despite post-HSCT complications, both recovered without sequelae. Five years post-HSCT, patient 1 is in complete remission (CR) off medications. Patient 2 was in CR until 11 months post-HSCT after which he developed three disease flares. At 4 years post-HSCT he is currently in CR on Adalimumab monotherapy. Engraftment was excellent with donor chimerism of 100%/patient 1 and 93 %/patient 2. In the literature, the outcome of allo-HSCT is reported in 13 sJIA patients (1-3). When merging those with our 2 patients, 1/15 patients died, 13/14 achieved CR, of which 12 are off medications (median [range] follow-up: 2.2 [0.2-7.0] years). Extended follow-up data on 11 of the 13 reported sJIA patients showed that an additional 3 patients flared at 3, 4 and 10 years post-HSCT (4). Conclusion: We report two patients with severe/refractory sJIA who underwent successful allo-HSCT and achieved CR. Allo-HSCT is a potential curative option for severe/refractory sJIA. It should be considered only after failure of conventional sJIA treatments and when an HLA-matched donor is available in order to lower transplant-related mortality. Outcome of reported sJIA patients who received allo-HSCT is encouraging but long-term follow-up data is needed to better characterized the risk-benefit ratio of this procedure.